Enforcing open source software licenses as a contributor - Lahtinen, Ilari (My University, 2020)
The importance of open-source software licenses has increased over recent years. One reason for the trend is the companies are more and more interested in open-source software. At the same time, with the increased use of the open-source license also disputes relating to them have increased. In my master thesis, I aim to discover who and within which limitations can raise a claim in the case of open-source software license infringement. Main research questions in my thesis are what are requirements for the open-source software project contributor to raise a claim in case of license infringement and on the other hand in which extend the contributor can raise a claim. The thesis also discovers whether every contributor has to be involved in raising the claim and running the case in the court. In other words, the question is whether one contributor may run the case on behalf of all contributors as a class action or some else way. Another perspective in the thesis is in which form the contributor have copyrights to the open-source code they have contributed. It is discovered whether source code is considered as collective work, jointly authored work or adaptive work when contributions are made over time. The thesis covers both relevant Finnish and European Union legislation. Also, some US legislation and case law are included as a preference because contributing open-source projects is an international phenomenon. The thesis also discovers what are the differences between legal and technical perspective when it comes to the open-source software development process and its result, the software. The outcome of the thesis is that every contributor has to take part in the infringement dispute process because it is not possible to run class action about an intellectual property dispute. There is also no way to move right to raise a claim to someone other with the contract, and therefore, that kind of action is not possible in license infringement cases either. One point which is also noticeable is that to get the right to raise a claim; the contributor must contribute to the project such that the contribution is intellectual enough to be alone protected with the copyright.

Avoimen lähdekoodin lisenssien merkitys ohjelmistotuotannossa on kasvanut viime vuosina. Syynä tähän on ollut yritysten kasvanut kiinnostus avointa lähdekoodia kohtaan. Samalla, kun avoimen lähdekoodin ohjelmistojen käyttö on lisääntynyt myös niihin liittyvät lisenssiriidat ovat lisääntyneet. Tutkielmassa tarkoituksena on selvittää kuka ja missä laajuudessa voi nostaa kanteen lisenssirikkomuksen sattuessa. Tutkielman keskeisimpinä tutkimuskysymyksiä käsittelevät sitä, miten avoimen lähdekoodin sovelluksen kehittämiseen osallistunut henkilö voi lähteä ajamaan kannetta lisenssin loukkaustilanteessa ja toisaalta, mitkä ovat edellytykset tälläisen kanteen nostamiselle. Selvitettävänä on täytyykö kaikkien kehittäjien osallistua kanteen nostamiseen ja sitä mahdollisesti seuraavaan oikeusprosessiin vai voiko yksi kehittäjistä ajaa asiaa kaikkien puolesta esimerkiksi joukkokanteena. Tutkielmassa käsitellään myös sitä, millaisen kokonaisuuden avoimen lähdekoodin ohjelmisto muodostaa tekijänoikeusnäkökulmasta. Tässä erityisenä tutkimuksen kohteena on se, muodostuuko ohjelmistosta yhteisteos, kokoelmateos vai muunnettu teos, kun sen kehittämiseen osallistuu useita kehittäjiä mahdollisesti eriaikoina. Tutkielma keskittyy Suomen ja Euroopan Unionin lain säädäntöön, mutta eräissä kohdissa myös Yhdysvaltojen lainsääntöä on käytetty vertailukohtana sillä avoimen lähdekoodin sovellusprojektit ovat yleensä kansainvälisesti kehitettyjä. Tutkielmassa tutkitaan myös, miten oikeustieteellinen näkökulma avoimen lähdekoodin sovelluksen syntymisestä poikkeaa teknisestä näkökulmasta ohjelmiston synnystä. Tutkielma päätyy johtopäätökseen, että jokaisen avoimen lähdekoodin kehittäjän tulee omalta osaltaan ajaa kannetta lisenssiehtojen rikkomistilanteessa, koska suomalainen lainsäädäntö estää joukkokanteen nostamisen muissa kuin kuluttajansuojariidoissa ja lisäksi myöskään kanneoikeuden siirtäminen sopimuksen avulla ei ole mahdollista. Kanneoikeutta rajoittaa myös se, että kehittäjän panoksen ohjelmistoon täytyy itsessään olla sellainen, että se ylittää ohjelmiston lähdekoodille asetetun teoskynnyksen.
Keywords: Open source license, Copyright, Intellectual property right litigation